Joint attention and its linguistic representation in dialogue: embodiment revisited - Zeng, Guocai (Frontiers in Psychology, 2023)
Lakoff and Johnson, among many others, have discussed the role of the human body in structuring meaning in communication, aiming to reveal the interrelation between the human body, language, and cognition. This study revisits the concept of embodiment and investigates its interactive nature functioning in speakers constructing repeated structures in conversation, based on the hypothesis made in this work that the joint attention of interlocutors essentially indicates the interaction of their embodied experience of the language used in the situated context, where speakers not only share their propositional commitments but also make individual contributions to establishing common ground in dialogue. Viewed in this way, at the linguistic level, the implicitly and/or explicitly repeated language resources displayed between utterances are in fact the encoding of speakers’ co-construction of joint attention and demonstrate the interplay of speakers’ syntactic and pragmatic knowledge in producing utterances in the talk turns. This research hopefully sheds some light on studies concerning the relationship between language and cognition as well as how language is constructed in dialogue from the interactive view of the syntax–pragmatics interface.